2011
DOI: 10.1007/s00264-011-1337-0
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional-CT evaluation of femoral neck anteversion, acetabular anteversion and combined anteversion in unilateral DDH in an early walking age group

Abstract: Femoral derotational osteotomy seems not to be necessary in Tönnis II and III types in unilateral DDH. Femoral derotational osteotomy should be considered in DDH, especially in Tönnis IV type, if the CA is still above 62° and the hip joints present instability in operation after abnormal acetabular anteversion, acetabular index and acetabular coverage of the femoral head are recovered to normal range through pelvic osteotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
2
34
0
1
Order By: Relevance
“…We would like to know whether any radiographic analysis was done preoperatively to assess the femoral anteversion. In our experience, we found that femoral anteversion is rarely exaggerated in DDH of the early walking age group,2 and this is in coordinance with other radiographic studies 34. Secondly, the author's method of assessing the need for derotation seems a little unclear.…”
supporting
confidence: 74%
“…We would like to know whether any radiographic analysis was done preoperatively to assess the femoral anteversion. In our experience, we found that femoral anteversion is rarely exaggerated in DDH of the early walking age group,2 and this is in coordinance with other radiographic studies 34. Secondly, the author's method of assessing the need for derotation seems a little unclear.…”
supporting
confidence: 74%
“…With great interest we read the article, "Three dimensional CT evaluation of femoral neck anteversion, acetabular anteversion and combined anteversion in unilateral DDH in an early walking age group" by Jia et al [1], published in your esteemed journal International Orthopedics. First of all, we would like to congratulate the authors for an excellent study.…”
mentioning
confidence: 99%
“…By using reconstruction techniques based on the special software, the orthopedic surgeon can inspect the anatomy from any desired angle and any section. Previously, we have reported that the three-dimensional computed tomography (3D-CT) showed better intra-and interobserver agreement than 2D-CT for assessing acetabular and femoral anteversion in DDH [16][17][18]. Therefore, the authors intend to employ 3D-CT and conventional plain Wlms evaluating the femoral head coverage in the present study.…”
Section: Introductionmentioning
confidence: 91%